2005
DOI: 10.7202/011336ar
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Participation in Non-Mandatory Training

Abstract: Tous droits réservés © Département des relations industrielles de l'Université Laval, 2004Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de l'Université de Montréal, l'Université Lav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
2
18
0
7
Order By: Relevance
“…The coefficients of the separate probit estimations for participation in orientation and training that improves/increases current skills are shown in columns 3 through 6. Consistent with previous findings (e.g., Renaud, Lakhdari, & Morin, ), we find that, compared to women, men working in the public sector are less likely to undertake any job training (column 1) and also less likely to undertake training that improves/increases current skills, irrespective of whether they work in the public or the private sector (columns 5 and 6). However, the estimated coefficient in column 3 suggests that male public‐sector employees are significantly more likely than female employees to participate in orientation training.…”
Section: Resultssupporting
confidence: 90%
“…The coefficients of the separate probit estimations for participation in orientation and training that improves/increases current skills are shown in columns 3 through 6. Consistent with previous findings (e.g., Renaud, Lakhdari, & Morin, ), we find that, compared to women, men working in the public sector are less likely to undertake any job training (column 1) and also less likely to undertake training that improves/increases current skills, irrespective of whether they work in the public or the private sector (columns 5 and 6). However, the estimated coefficient in column 3 suggests that male public‐sector employees are significantly more likely than female employees to participate in orientation training.…”
Section: Resultssupporting
confidence: 90%
“…tabela 1. Źródło: opracowanie własne na podstawie: [Green, 1993;Blundell, Dearden, Meghir, 1996;Oosterbeek, 1998;Shields, 1998;Harris, 1999;Leuven, Oosterbeek, 1999;Nisar, 2004;Renaud, Lakhdari, Morin, 2004;Almeida-Santos, Mumford, 2005;Asplund, 2005;Bassanini i in. 2005;Litwiński, 2007;Franck, Nüesch, Pieper, 2009;Backes-Gellner, Oswald, Tuor, 2011;Thangavelua i in.…”
Section: Czynniki Wpływające Na Uczestnictwo Pracowników W Szkoleniachunclassified
“…That is, the profitability of training decreases with age because a younger worker has more years to amortize her/his training investments (Renaud et al, 2004). Renaud et al (2004) showed that age negatively influenced training participation. In our study, this discussion can be applied to training for entrepreneurs directly.…”
Section: Entrepreneurial Characteristicsmentioning
confidence: 99%